Colour-Guidelines for the University of Malaya: Focusing on University Identity - Kim, Yoosun; Md Akhir, Md Nasrudin; Kim, Yoomi (WILAYAH: The International Journal of East Asian Studies, 2019)
This study presents a suggested array of colour guidelines for the university homepage of the University of Malaya (UM) in Malaysia which represents the school’s distinction and brand image. The importance of University Identity on institutional websites is to secure their identity and differentiation from other institutions. Despite having a multicultural heritage, it is difficult to find colour guidelines of any universities in Malaysia. There are limited studies on the colour analysis of UM as one of the top public universities in Malaysia. We suggest colour guidelines using 18 types of primary colours, sub-colours, and second colour for the UM website that we believe would further reflect its University Identity, its status as well as enhance the nature of multicultural outlook of the institution. Accordingly, this study will have an academic and policy-level significance not only for Malaysia but other international institutions as well.